Wage Inequality, Intergenerational Mobility, and Education in Singapore - HO, Kong Weng (Institutional Knowledge at Singapore Management University, 2007)
Accompanying Singapore’s phenomenal economic growth over the past four decades has been a rapid increase in educational attainment over the years. In 1960, the mean years of schooling for residents aged 25 and over was 3.14 years; in 2006, it was 9.3 years. This dramatic increase in the supply of skilled labour in all sectors of the economy helped to power Singapore’s high growth rates over the past few decades of economic development, which also saw declining wage inequality and high upward intergenerational mobility in education. However, we need to ask if these trends will continue in the future and whether underlying socioeconomic and demographic changes may challenge or reverse the macroeconomic dynamics underlying Singapore’s past decades of growth.